Pengaruh Marinasi Ekstrak Buah Andaliman (Zanthoxylum acanthopodium DC.) terhadap Jumlah Total Bakteri, Awal Kebusukan dan Akseptabilitas pada Daging Babi - Tiorugun Marpaung; Lilis Suryaningsih; Andry Pratama (Jurnal Teknologi Hasil Peternakan, 2022)
Andaliman contains active compounds including flavonoids, glycosides, tannins, and has a unique taste, which is a spicy blend with the lemon flavor can be used as a natural preservative to reduce the number of bacteria, prolong the time of rot and the acceptability of meat. The aim of the study was to determine the effect of using the different concentrations of andaliman fruit extract and to determine the best concentration that could reduce the total number of bacteria, delay the onset of spoilage and maintain acceptability. The experimental study used a completely randomized design, with four concentrations of andaliman fruit extract; 0% (P1), 0.25% (P2), 0.50% (P3), and 0.75% (P4). Analysis of variance was used to determine the effect of the andaliman extract concentration on total plate count and the onset of spoilage. The differences between the treatments were observed using Duncan’s multiple range test. The acceptability was analyzed using Kruskal-Wallis’s test and Mann-Whitney’s test. The results showed that the marination using andaliman extract at 0.75% gave the best results in terms of total plate count of 7,9 x 106 cfu/g, the onset of spoilage at 717 minutes and acceptability by the panelists.